2021
DOI: 10.1021/acsami.1c04335
|View full text |Cite
|
Sign up to set email alerts
|

Tremella-like Mo and N Codoped Graphitic Nanosheets by In Situ Carbonization of Phthalocyanine for Potassium-Ion Battery

Abstract: A tremella-like Mo and N codoped graphitic nanosheet array supported on activated carbon (Mo2C-MoC/AC-N) is prepared via in situ carbonization of nitrogen-rich cobalt phthalocyanine nanoparticulates anchored on activated carbon as a high-performance anode for potassium-ion batteries. The nanosheets about 5 nm thick are uniformly distributed on the surface of activated carbon for fast K-ion intercalation, and the abundant micropores in activated carbon provide additional adsorption sites of potassium ions, form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Metal naphthalocyanine is a large π-conjugated aromatic system that was originally used as pigment and is widely used in optical and electrical fields owing to its absorption characteristics in the near-infrared region. Metal naphthalocyanine species comprise a central metal and ligand, which is obtained by adding four benzene rings to the phthalocyanine, and have a larger conjugated structure than those of phthalocyanines. Moreover, they are ideal precursors for N-doped C. , Monodispersed central metal ions prevent the agglomeration of metal-oxide particles during formation and cycling . Metal naphthalocyanine species show promise as sacrificial precursors with tunable functionalities to fabricate tailorable metal-oxide/carbon materials with unique structures in the construction of various architectured electrode materials for LIBs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal naphthalocyanine is a large π-conjugated aromatic system that was originally used as pigment and is widely used in optical and electrical fields owing to its absorption characteristics in the near-infrared region. Metal naphthalocyanine species comprise a central metal and ligand, which is obtained by adding four benzene rings to the phthalocyanine, and have a larger conjugated structure than those of phthalocyanines. Moreover, they are ideal precursors for N-doped C. , Monodispersed central metal ions prevent the agglomeration of metal-oxide particles during formation and cycling . Metal naphthalocyanine species show promise as sacrificial precursors with tunable functionalities to fabricate tailorable metal-oxide/carbon materials with unique structures in the construction of various architectured electrode materials for LIBs .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are ideal precursors for N-doped C. 18,19 Monodispersed central metal ions prevent the agglomeration of metal-oxide particles during formation and cycling. 20 Metal naphthalocyanine species show promise as sacrificial precursors with tunable functionalities to fabricate tailorable metal-oxide/ carbon materials with unique structures in the construction of various architectured electrode materials for LIBs. 21 Metaloxide microcrystals exhibit short Li + transport pathways, and the accessible surface area of the active materials is large.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6,16,26,27 However, the catalytic activity of conventional MPcs, including cobalt phthalocyanine (CoPc), iron phthalocyanine (FePc), nickel phthalocyanine (NiPc) with bulk morphology is limited, far from the requirements of Li/SOCl 2 battery. 5,17,27,28 Several works have been shown that MPc with optimized substitutes, including MPcCl 4 , MPc-COOH, and nitrogen-rich MPc (e.g. metal tetrapyridinoporphyrazine (MTAP)) could achieve a higher activity due to more electrons contributed to the conjugate systems.…”
mentioning
confidence: 99%